Prevalence of bronchial asthma in Indian children - Pal Ranabir; Dahal Sanjay; Pal Shrayan (Wolters Kluwer Medknow Publications, 2009)
Background: The prevalence of childhood bronchial asthma and allergic disease has increased in developed countries. Studies have identified asthma among Indian children. Still, there is paucity of information on the overall prevalence of childhood asthma in India. Objective: To assess time trends and the overall prevalence rate of bronchial asthma among Indian children. Materials and Methods: Literature search for data sources was done through an extensive search in indexed literatures and website-based population survey reports. Fifteen epidemiological studies were identified on the development of asthma in Indian children from 300 potentially relevant articles. A broad criterion to define both allergic and non-allergic descriptions of asthma in Indian children was formed. Moreover, in the absence of universally accepted criteria by reporting of prevalence by researchers, weighted average data was considered during calculations of prevalence rates, irrespective of the criteria for diagnosis. Statistical analyses used were mean and median. Results: Wide differences in samples, primary outcome variables, lack of consistency in age category, rural-urban variation, criteria for positive diagnosis, and study instruments confounded the outcome variables. The mean prevalence was 7.24 ± SD 5.42. The median prevalence was 4.75% [with IQR = 2.65 - 12.35%]. Overall weighted mean prevalence was found to be 2.74. Childhood asthma among children 13 - 14 years of age was lower than the younger children (6 - 7 years of age). Urban and male predominance with wide inter-regional variation in prevalence was observed. Conclusions: Our findings indicate that the burden of bronchial asthma in Indian children is higher than was previously understood.